TEACHER’S EXPLORATION ON CRITICAL AND CREATIVE INQUIRY IN CHILD EDUCATION: CHALLENGES FROM DIGITAL DISRUPTION IN 21st CENTURY LEARNING - Hayeesama-ae, Solihah; Chenu, Ilham (PERINTIS eJournal, 2023)
Using critical inquiry in teaching while living with the impact of digital disruption is a complex undertaking and challenging for teachers. This paper dives into teachers’ thoughts and experiences on how the drastic changes in education trends impact their classroom teaching and the influence of blended IT in their teaching methodology. The findings also proposed the possibility of teaching child education shifting from implementing pedagogy into practicing andragogy. With the introduction of analysis of life experience and self-directed learning, it enables teachers to accept the new challenges and actively seek or request for the new perspective and new understanding which are fundamental to the process of change.